2022
DOI: 10.1364/oe.459332
|View full text |Cite
|
Sign up to set email alerts
|

Laser processing of microdroplet structure of liquid crystal in 3D

Abstract: Processing of mesoscale structures of soft matter and liquid is of great importance in both science and engineering. In this work, we introduce the concept of laser-assisted micromachining to this field and inject a certain number of microdroplets into a preselected location on the surface of a liquid crystal drop through laser irradiation. The impact of laser energy on the triggered injection is discussed. The sequentially injected microdroplets are spontaneously captured by the defect ring in the host drop a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The TAMI phenomenon is caused by the thermally induced Marangoni effect. Laser-induced water injection across the LC–water interface, introduced by the photothermally controlled Marangoni effect, has been studied in previous works. , It has been demonstrated that the injection site is determined by the laser irradiation area, where a sufficient temperature gradient is established. To understand the temperature distribution introduced by the TAMI method, we perform a FEM simulation (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The TAMI phenomenon is caused by the thermally induced Marangoni effect. Laser-induced water injection across the LC–water interface, introduced by the photothermally controlled Marangoni effect, has been studied in previous works. , It has been demonstrated that the injection site is determined by the laser irradiation area, where a sufficient temperature gradient is established. To understand the temperature distribution introduced by the TAMI method, we perform a FEM simulation (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…21,22 With the help of the elasticity of the LC molecules, the injected solution spontaneously forms into monodispersed guest droplets which latter self-assemble into substructures along the director field of the host LC droplet. 20,21,23 However, this approach requires an external laser system. Producing MDEs at low cost and high rates remains challenging.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the Laser injection technique brings the concept of laser micro-nano manufacturing to the field of soft matter and injects water droplets into an LC droplet using a laser beam. [2][3][4] As the director field of the LC droplet is stabilized, the injected water droplets will self-assemble into an organized structure. But it requires a dedicated laser system and the processing efficiency is relatively low due to its serial nature.…”
Section: Introductionmentioning
confidence: 99%
“…Within the visible light band, the feasibility of core-shell microspheres to form ultra-long photonic nanojets has been demonstrated 14 , inspiring our endeavor to apply this structure in THz band. Moreover, the progress in microfabrication technology expands the horizons for creating core-shell microspheres [15][16][17][18] . This study initially confirms the capability of core-shell microspheres to produce long terajets.…”
Section: Introductionmentioning
confidence: 99%